PENGARUH SUMBER DAYA & FAKTOR PENDUKUNG TERHADAP DAYA TARIK OBJEK WISATA KANDI KOTA SAWAHLUNTO - Kurnia Illahi Manvi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Resources factors and attraction or core resources and states in order to attractors event in a tourist destination , includes: phsysiography and climate , culture and history , market ties , mix of activities , the tourism suprastructure by factors in support of and resources ( supporting factors and states in order to resources event in a tourist destination, includes: infrastructures , accessibility , facilitating resources , hospitality and politic will. The methodology used in this study is descriptive quantitative to see the condition of core resources and attractors and supporting factors in tourist destinations Kandi Tourism Object of Kota Sawahlunto, correlation method to see the relationship between the factor itself and its relationship with tourist destination Object Kandi Kota Sawahlunto regresional method to find out how big the influence of core resources and attractors factors and supporting factors that exist on the tourist attraction in Kandi Sawahlunto Tourism Object. The result of the research is the development of tourism object conducted by the Department of Tourism and Culture of Sawahlunto City in the Tourism Object of Kencana Kota Sawahlunto has started to show good development seen from the course resources and attractors and supporting factors is 51%. Factors that influence the attractiveness tourist destinations Kandi Sawahlunto Tourism Objects are the variables that exist in course resources and attractors and supporting factors are very significant effect on tourist attraction, such as culture and history variables, mix of activity and infrastructure.